2020
DOI: 10.1002/prp2.621
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, potentially serious clinically relevant drug‐drug interactions, and inappropriate medicines in elderly people with type 2 diabetes and their impact on quality of life

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
2
33
0
2
Order By: Relevance
“…In multi-pathological patients, where polypharmacy is so common, published studies assessing the usefulness of drug interaction screening programs are very limited [4, 5]. Our results demonstrated that in patients with that profile, discrepant results among those programs are also very common; differences among the 3 programs we assessed were so extent that comparison among them was virtually unfeasible, with the exception, perhaps, of Medscape and Drugs, where findings were partially similar.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In multi-pathological patients, where polypharmacy is so common, published studies assessing the usefulness of drug interaction screening programs are very limited [4, 5]. Our results demonstrated that in patients with that profile, discrepant results among those programs are also very common; differences among the 3 programs we assessed were so extent that comparison among them was virtually unfeasible, with the exception, perhaps, of Medscape and Drugs, where findings were partially similar.…”
Section: Discussionmentioning
confidence: 67%
“…Polypharmacy not only increases the likelihood of drug interactions and adverse drug events but also associated with drug administration errors and nonadherence [12]. Those problems may affect patients of any age, but they are particularly prevalent in the elderly, where decline in elimination organ’s function, metabolic changes, and cognitive deficit are common [2, 5, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the enrolled samples was about 75 years, except for the work of McCracken et al [ 21 ], performed on older patients (mean age 85 years). Concerning the definition of polypharmacy, four studies considered the usual consumption of 5 or more medications per day [ 13 , 14 , 18 , 20 , 22 ], two studies of > 5 drugs/ day [ 17 , 19 ], one of ≥ 4 drugs/day [ 4 ], and one of ≥ 9 drugs per day [ 21 ]. One work reported the median number of medications taken, but not the frequency of polypharmacy [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients presenting with several chronic conditions such as psychiatric disorders, cardiovascular disorders, diabetes, and rheumatoid arthritis often require multiple therapeutic approaches, including the use of numerous drugs, to achieve clinical benefits and experience favorable outcomes [ 1 , 2 , 3 , 4 ]. The co-administration of multiple drugs required to treat complex conditions and associated comorbidities can lead to major pharmacokinetic and/or pharmacodynamic drug–drug interactions (DDIs) [ 5 , 6 , 7 ]. These circumstances also impact drug safety, adherence, and efficacy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%